Deficit irrigation and leaf removal modulate anthocyanin and proanthocyanidin repartitioning of Cabernet Sauvignon (Vitis vinifera L.) grape and resulting wine profile. (20th November 2021) - Duan, Bingbing; Mei, Yuan; Chen, Guoqiao; Su‐Zhou, Chenxing; Li, Yashan; Merkeryan, Hasmik; Cui, Ping; Liu, Wei; Liu, Xu
Abstract: BACKGROUND: In monsoonal climates, grape anthocyanin and proanthocyanidin (PA) accumulations are unsatisfactory for producing optimal wine. Agronomical practices are often considered to be effective means for regulating fruit components. However, there is a lack of quantitative information on the effects of deficit irrigation (DI), basal leaf removal (LR) or their combination of deficit irrigation and leaf removal (DILR) on the characteristics of anthocyanin and PA compositions and their implications on the resulting wine quality. In this study, the dynamics of grape anthocyanin and PA accumulation were investigated in DI, LR and DILR during grape ripening, and the resulting wine profile was assessed. RESULTS: The contents of reducing sugar and total anthocyanins in Cabernet Sauvignon berries were significantly increased by DI, LR and DILR, while titratable acidity, total flavan‐3‐ols and tannins levels were generally decreased. Notably, the levels of 3′5′‐substituted anthocyanins, such as malvidin and its derivatives significantly increased, and 3′‐substituted anthocyanins decreased in both grape and wine under DI and DILR strategies. Skin PAs were sensitive to water deficits, whereas they were insensitive to LR. In resulting wine, PAs content and the proportion of 3′‐hydroxylated PAs, such as (+)‐catechin, (−)‐epicatechin and (−)‐epicatechin‐3‐ O ‐gallate units were significantly decreased under DI and DILR, while molecular mass and the proportion of 3′5′‐hydroxylated units of PAs were increased in response to DILR. CONCLUSION: The DILR was the most favorable for the repartitioning of anthocyanin and PA metabolites, and promoted the accumulation of tri‐substituted forms contributing a higher color intensity, mouthfeel persistence, structure, and astringency of wine. This information provides an important strategy for modulating the anthocyanin and PA compositions by agricultural practices and achieving the desired quality of grapes and wines in monsoonal climates. © 2021 Society of Chemical Industry.